ISTISHAB SEBAGAI METODE ISTINBAT HUKUM - Faisol Rizal; Salim Ashar (Minhaj: Jurnal Ilmu Syariah, 2023)
Problems in a pluralistic society demand solutions that are produced through systematic and measurable methods. Problems are increasingly developing when the era has intersected with technology, social, behavior, politics as well as ways of thinking and law from the West. The theory of modernity as mentioned by Lucian W. Pye is characterized by the first, cutting-edge technology and scientific spirit. Second, a rational view of life. Third, a secular approach in social relations. Fourth, there is a balanced fairness in public affairs. Fifth, the realization and implementation of a system of government in the configuration of a nation state. Therefore, in answering worldly problems which are increasingly leading to complexity and diversity, ijtihad is needed. Ijtihad is the basis and means of developing Islamic law. Ijtihad is also an obligation for Muslims who have fulfilled the requirements (because they have fulfilled the capacity as a mujtahid) to fulfill it. The methods used in this article is a qualitative approach to the library, where the focus is aimed against any reference about the religion, culture and islamic boarding school. The approach used is qualitative, which is a research procedure that describes the behavior of certain people, events, or places in detail and depth. While this type of research is literature. Namely, research that relies on reading sources, texts, and various information in the form of reading. In a different reference library research is research that is done to solve a problem that is based on a critical study of library materials and related research results presented in new ways.